Long‐term follow‐up of patients treated with entecavir and peginterferon add‐on therapy for HBeAg‐positive chronic hepatitis B infection: ARES long‐term follow‐up. Issue 1 (27th September 2018) - van Campenhout, Margo J. H.; Brouwer, Willem Pieter; Xie, Qing; Guo, S.; Chi, Heng; Qi, Xun; Tabak, Fehmi; Streinu‐Cercel, Adrian; Wang, Ji‐Yao; Zhang, Ning‐Ping; Idilman, Ramazan; Reesink, Hendrik W.; et al.
Summary: Addition of peginterferon alpha (PEG‐IFN add‐on) to entecavir (ETV) treatment after a short lead‐in phase results in more response than ETV monotherapy in HBeAg‐positive chronic hepatitis B infection (CHB). This study is the first to assess long‐term efficacy of this treatment strategy. Patients who received ETV ± 24 weeks of PEG‐IFN add‐on in a global trial (ARES study) and completed follow‐up were eligible to participate in this observational LTFU study if they had at least one combined HBeAg and HBV DNA measurement beyond week 96 of the ARES study. The primary endpoint was combined response (HBeAg loss and HBV DNA <200 IU/mL) at LTFU. In total, 48 patients treated with PEG‐IFN add‐on and 48 patients treated with ETV monotherapy were included. The median follow‐up duration was 226 (IQR 51) weeks, and 86/96 (90%) patients were initial non‐responders. At LTFU, combined response was present in 13 (27%) vs 11 (23%) patients ( P = 0.81), and 1 log10 HBsAg decline in 59% vs 28% ( P = 0.02) for PEG‐IFN add‐on and ETV monotherapy, respectively. In 41 initial non‐responders who continued ETV therapy, combined response at LTFU was present in 9 patients (PEG‐IFN add‐on: 5/22 [23%]; ETV monotherapy: 4/19 [21%]). Beyond week 96 of follow‐up, rates of serological response became comparable between PEG‐IFN add‐on and ETV monotherapy. Although in this LTFU study initial non‐responders were overrepresented in the add‐on arm, PEG‐IFN add‐on possibly leads rather to accelerated HBeAg loss than to increased long‐term HBeAg loss rates.